Native MicroRNA Targets Trigger Self‐Assembly of Nanozyme‐Patterned Hollowed Nanocuboids with Optimal Interparticle Gaps for Plasmonic‐Activated Cancer Detection. Issue 50 (13th November 2019) - Li, Junrong; Koo, Kevin M.; Wang, Yuling; Trau, Matt
Abstract: The modernized use of nucleic acid (NA) sequences to drive nanostructure self‐assembly has given rise to a new class of designed nanomaterials with controllable plasmonic functionalities for broad surface‐enhanced Raman scattering (SERS)‐based bioanalysis applications. Herein, dual usage of microRNAs (miRNAs) as both valuable cancer biomarkers and direct self‐assembly triggers is identified and capitalized upon for custom‐designed plasmonic nanostructures. Through strict NA hybridization of miRNA targets, Au nanospheres selectively self‐assemble onto hollowed Au/Ag alloy nanocuboids with ideal interparticle distances (≈2.3 nm) for optimal SERS signaling. The intrinsic material properties of the self‐assembled nanostructures further elevate miRNA detection performance via nanozyme catalytic SERS signaling cascades. This enables fM‐level miR‐107 detection limit within a clinically‐relevant range without any molecular target amplification. The miRNA‐triggered nanostructure self‐assembly approach is further applied in clinical patient samples, and showcases the potential of miR‐107 as a non‐invasive prostate cancer diagnostic biomarker. The use of miRNA targets to drive nanostructure self‐assembly holds great promise as a practical tool for miRNA detection in disease applications. Abstract : Native microRNA targets directly trigger the assembly of Au nanospheres on hollowed Au‐Ag alloy nanocuboids with ideal interparticle gaps for surface‐enhanced Raman scattering detection. The self‐assembled plasmonic nanostructure enables specific and sensitive miR‐107 detection from prostate cancer patient samples without the need for target amplification.